2007
DOI: 10.1007/s00192-007-0527-1
|View full text |Cite
|
Sign up to set email alerts
|

Short-term efficacy and complications of posterior intravaginal slingplasty

Abstract: This study was performed to evaluate the efficacy and complications of the posterior intravaginal slingplasty (IVS). A retrospective chart review was performed. Ninety IVS procedures were performed from January 2004 to June 2005. The group consisted of predominantly nonsmoking, Caucasian, postmenopausal women with a median age of 62 years and a median parity of 3. The mean follow-up was 33 +/- 23.2 weeks with a median of 31.9 weeks. There were no intraoperative bladder, bowel, or vascular injuries. Overall, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…A short vagina is often not amenable to vaginal sacrospinous colpopexy [107]. Disadvantages of the IVS operation are usually related to the failure of the non-absorbable mesh to be secured, a high erosion rate of at least 18% [108,109], gluteovaginal fistula formation [110], and gluteo-vaginal sinus formation [111].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…A short vagina is often not amenable to vaginal sacrospinous colpopexy [107]. Disadvantages of the IVS operation are usually related to the failure of the non-absorbable mesh to be secured, a high erosion rate of at least 18% [108,109], gluteovaginal fistula formation [110], and gluteo-vaginal sinus formation [111].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…Several authors have reported retrospectively an unusually high rate of graft erosion or infection or both ranging from 4 -18% associated with use of the multifilament intravaginal slingplasty tape. 2,4 Serious graft complications leading to retropubic abscess, vesicovaginal fistula, and cutaneous suprapubic fistula have been reported. 5 This case is unique because the infection presented outside of the pelvis, thus not alerting us of its relationship to a previous implant.…”
Section: Commentmentioning
confidence: 98%
“…Like with our patient, other authors have reported that excision of infected grafts does not necessarily result in prolapse recurrence in short-term follow-up studies. 2,3 Knowing the composition of synthetic implanted materials and their biologic behavior is essential for the appropriate selection of graft materials for incontinence and prolapse surgery and fundamental for the effective management of postoperative complications. This case report illustrates the importance of maintaining a high index of suspicion in patients with atypical infections in sites remote from the original operative site in those with either recent or remote reconstructive pelvic surgery using non-type I synthetic mesh materials.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Luck et al [6] étudient une série de 90 patientes traitées par IVS postérieur pour prolapsus apical de stade supérieur ou égal à 1 (Baden et Walker). Une prothèse antérieure est associée dans 66,6 % (60/90) des cas.…”
Section: éTudes Rétrospectivesunclassified